Enhancing financial performance of halal MSMEs through intellectual capital and business sustainability in Medan City, Indonesia‎ - Siregar, Retnawati; Ramadhan, Muhammad; Kamilah, Kamilah (Journal of Islamic Economics Lariba, 2025)
IntroductionThe rapid global growth of the halal industry has highlighted the increasing demand for ethical, sharia-compliant products and services. In Indonesia, particularly Medan City, halal-certified micro, small, and medium enterprises (MSMEs) have emerged as key contributors to the local economy. Despite holding halal certifications, many of these enterprises struggle to optimize their financial performance, indicating that certification alone is insufficient for success. This study investigates the role of intangible assets—intellectual capital and business sustainability —in enhancing the financial outcomes of halal MSMEs.ObjectivesThis research examines the influence of intellectual capital, comprising human capital, structural capital, relational capital, and spiritual capital, along with business sustainability, on the financial performance of halal MSMEs in Medan City. It seeks to determine the components that significantly impact performance and provide practical insights for improving business competitiveness in the halal sector.MethodThis study adopted a Sequential Explanatory design using a mixed-methods approach. Quantitative data were collected through 219 structured questionnaires distributed to halal-certified food and beverage MSMEs in Medan, whereas qualitative data were obtained from 51 in-depth interviews with MSME owners and employees. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and thematic coding with NVivo 12 Plus software.ResultsThe findings show that human capital, structural capital, relational capital, and business sustainability have significant and positive influences on the financial performance of halal MSMEs. However, spiritual capital did not have a statistically significant effect. The model explains 51.2% of the variance in financial performance. Qualitative insights revealed that, while spiritual capital may not directly impact financial performance, it strengthens ethical values and trust, indirectly supporting relational capital.ImplicationsThe results underscore the importance of investing in human resources, optimizing organizational systems, building strong external relationships, and integrating sustainable business practices. These strategies can improve financial performance, resilience, and long-term viability in a competitive and ethically conscious market environment.Originality/NoveltyThis study makes a novel contribution by expanding the Intellectual Capital framework to include Spiritual Capital and Business Sustainability in the context of halal MSMEs. This is one of the first empirical studies to examine this integration using a mixed-methods approach, providing both theoretical enrichment and practical guidance for MSME development in the halal economy.